Study on the community structure of macrozoobenthos in Kobok and Kao estuaries, Kao Bay, North Halmahera - Talib, Najib Hi; Lumingas, Lawrence J.L; Lasut, Markus T (Universitas Sam Ratulangi, 2014)
This study aims to assess the community structure of macrozoobenthos in the estuary of Kobok and Kao rivers, Kao Gulf waters. Sampling was carried out in October 2014 at 10 sampling stations in both estuaries. Variables examined in this study were community variables, such as species composition and abundance, including species diversity index Shannon-Wiener (H '), species richness (SR) index, evenness index (J'), Berger-Parker dominance index (d) and 'assemblage' (group) of the macrozoobenthos using multivariate analysis such as classification and analysis of factorial correspondence analysis (AFK). This study obtained a total of 757 individuals of 61 species. Diversity Index (H ') ranged from 1.62 to 3.96, Evenness index (J ') from 0.63 to 1.26., richness (SR) index ranged from 2.83 to 4.45 and dominance index (d) 0.16 to 0.47. Classification analysis separated 4 interconnecting groups at the station or resident species that were in the similar sediment types. Correspondence Factorial Analysis for the station variables mostly responsible for the axial formation was stations mostly contributing to the formation of axes as the characteristic station of the axes, because it had relatively high contribution. Penelitian ini bertujuan untuk menilai struktur komunitas makrozoobentos di muara Sungai Kobok dan muara Sungai Kao perairan Teluk Kao. Pengambilan sampel dilaksanakan pada bulan oktober 2014 pada 10 stasiun sampling di kedua muara. Variabel yang dikaji dalam penelitian ini adalah variabel komunitas seperti komposisi dan kelimpahan spesies termasuk indeks keanekaragaman spesies Shannon-Wiener (H’), indeks kekayaan spesies (SR), indeks kemerataan spesies (J’), indeks dominasi Berger-Parker (d) serta ‘assemblage’ (grup) makrozoobentos dengan menggunakan analisis multivariate seperti analisis klasifikasi maupun analisis faktorial koresponden (AFK). Penelitian ini diperoleh total 757 individu yang termasuk dalam 61 spesies. Nilai Indeks Keanekaragaman (H’), berkisar dari 1.62-3,96. Nilai Indeks Kemerataan Spesies (J’), berkisar dari 0,63-1,26. Nilai Indeks kekayaan spesies (SR), berkisar dari 2,83-4,45 dan Nilai indeks dominasi (d), berkisar dari 0,16-0,47. Analisis klasifikasi telah memisahkan 4 grup yang saling berhubungan pada stasiun maupun spesies penghuni yang memiliki kemiripan dalam tipe sedimen. Sedangkan Analisis Faktorial Koresponden untuk variabel stasiun yang paling bertanggungjawab terhadap pembentukan sumbu-sumbu adalah (kontribusi absolut). Stasiun-stasiun yang paling berkontribusi dalam pembentukan sumbu juga sebagai stasiun karakteristik sumbu tersebut, karena memiliki kontribusi relatif yang juga tinggi.